Distribution of Number, Location of Pain and Comorbidities, and Determinants of Work Limitations among Firefighters. (9th November 2020) - Nazari, Goris; Osifeso, Temitope A.; MacDermid, Joy C.
Abstract : Introduction . The unique demands of firefighting results in acute, recurrent, or chronic pain complications. We aimed to describe the percentage distribution of number and location of painful sites among FFs and determine whether work limitations differed based on the number or location of painful sites, age, and/or sex. Methods . About 325 firefighters completed a work limitation questionnaire (WLQ-26) and a checklist to indicate painful regions of the body using either a paper format or an online survey. A one-way ANOVA was employed to analyze the transformed work limitation scores; this was a two-sided test with a significance level of <0.05, to determine if work limitations differed among firefighters based on the number or location of painful sites, age, and/or sex. Results . The data analyzed consisted of 325 (men = 216, women = 109 ) FFs in total. The percentage distribution of the number of painful sites in our study cohort was 43% no pain, 17% one painful site, 19% two painful sites, and 21% three or more painful sites. The percentage distribution of the locations of painful sites was 43% no pain, 41% spine, 9% lower extremity, and 7% upper extremity. An estimated 31% of FFs (n = 102 ) reported non-MSK comorbidities with 23% (n = 76 ) reporting at least one non-MSK comorbidity and 8% (n = 26 ) reported having two or more comorbidities. FFs > 45   years of age experienced more physical work limitations than FFs ≤ 45 years (mean difference: 0.74/10; 95% CI .19-1.29; p = 0.008 ). Conclusions . The majority of firefighters reported having at least one painful site and indicated the spine as the most common painful location. Age, the number of painful sites, and location of pain were identified as a potential contributor to physical/mental and work output limitations.